Avaliação entre consumo e ganho residual, desempenho e características de carcaça em bovinos da raça Nelore - Luis Miguel Gonçalves Fernandes (2020)
The objective of the present work was to evaluate the associations between performance and carcass traits in Nellore cattle, classified according to residual feed intake and gain (RIG). Data from 895 male Nellore cattle were evaluated, from 7 feed efficiency tests carried out from 2011 to 2014 at the Rancho da Matinha farm, in Uberaba-MG. A priori, residual feed intake (RFI) and residual gain (RG) were determined. From this, the RIG was calculated by adding (-1 * CAR) with the RG. The animals were grouped based on two different classes of RIG, efficient animals (> average + 0.5 standard deviation (SD), n = 275 animals) and inefficient animals (<average - 0.5 SD, inefficient; n = 291 ), and the rest were intermediate animals (mean ± 0.5 SD; n = 329), which were not included in the statistical calculation. The data were subjected to analysis of variance, and the comparison of means was performed by the Tukey test at 5% probability. Pearson correlations were estimated between performance, traits carcass and RIG classification. RIG-efficient animals showed greater daily weight gain (DWG) and greater ribeya area (RA) (P <0.001) compared to inefficient animals. Negative phenotypic correlations (P <0.001) between CGR and dry matter intake (DMI; r = -0.51) and RFI (r = -0.98) were observed. Thus, the RIG is a measure that can be used to identify and select animals with higher rates of weight gain, and greater RA, however it should be used with caution, as it may be related to the increase in body size and consequently increase the weight the maturity of the animals